Between conservation and production: peasant families of Tromen’s Protected Natural Area (Neuquén, Argentina) - María Preda, Graciela (2022)
Protected natural areas are traversed by conservation objectives and the dynamics of the populations inhabiting them. In El Tromen Park (Neuquén, Argentina) 30 families stay during the summer raising their animals. This article aims to reconstruct the trajectories and reproduction strategies of these peasant families and to know the environmental dynamics in the area and its problems. Identity and family trajectories are rooted within the socio-productive history of Neuquén’s northern area, and their forms of work organization are conditioned by being located in a protected space. The analysis was carried out mainly based on 15 semi-structured interviews with breeding families and key informants, and was complemented with a bibliographic review, compilation of official documents and interpretation of satellite images.